Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 10: Belkginoecetes gen. nov., Tropicoecetes gen. nov. and Rhinoecetes Just, 1983 from north-eastern and northern Australian shallow water, with eight new species - Just, Jean (Zootaxa, 2012)
Two new genera and eight new species of bubocorophiid Siphonoecetini are described from north-eastern and northernAustralia: Belkginoecetes bullockyensis gen. et sp. nov. B. cooee sp. nov. (type species), B. darwiniense sp. nov., B. fleu-rae sp. nov., B. solea sp. nov., B. springthorpei sp. nov., Tropicoecetes carinata gen. et sp. nov., Rhinoecetes anneae sp.nov. The concept of bubocorophiid siphonoecetids and their distribution along eastern and northern Australia is briefly discussed. A key to species of Belkginoecetes gen. nov. is presented.